An on-chip deformability checker demonstrates that the severity of iron deficiency is associated with increased deformability of red blood cells - Kenji Kajitani; Tomohito Ohtani; Rie Higuchi; Misato Chimura; Fusako Sera; Chia-Hung Dylan Tsai; Yasutaka Ueda; Jun-ichi Nishimura; Yasushi Sakata (Scientific Reports)
Abstract The deformability of red blood cells (RBCs) is essential for peripheral circulation and RBC survival and is reportedly altered in several diseases. However, its detail in iron-deficiency (ID) anemia remains poorly understood. We investigated the association between ID and RBC deformability in 120 participants classified into four groups according to their ferritin and hemoglobin levels: non-ID/non-anemia (n = 61), ID/non-anemia (n = 32), ID/anemia (n = 15), and non-ID/anemia (n = 12). In the analysis using the established on-chip deformability checker, the normalized transit velocity of RBCs through the peripheral-vessel constriction models was significantly higher in the ID/anemia group than in the other groups. The RBC deformability index (RDI), derived from the normalized transit velocity and degree of RBC deformation, was highest in the ID/anemia group, followed by the ID/non-anemia group. The RDI was negatively correlated with log10 ferritin levels (r = -0.66, p < 0.01), even after adjusting for hemoglobin levels. Lower log10 ferritin levels correlated with thinner, more oval-shaped RBCs and lower internal viscosity. These RBC characteristics were significantly associated with a higher RDI. These results suggest that, among several known determinants of RBC deformability, RBC morphology and internal viscosity are altered in ID, resulting in higher deformability.